Author Correction: A novel atypical sperm centriole is functional during human fertilization - Emily L. Fishman (Nature Portfolio, 2018)
In the original version of this Article, the affiliation details for Jadranka Loncarek and Vito Mennella were incorrectly given as ‘Cell Biology Program, The Hospital for Sick Children, Department of Biochemistry, University of Toronto, 555 University Avenue, Toronto, ON, M5G 1X8, Canada’ and ‘Laboratory of Protein Dynamics and Signaling, Center for Cancer Research, National Cancer Institute, 1050 Boyles Street, Frederick, MD, 21702, USA’, respectively. This has now been corrected in both the PDF and HTML versions of the Article.